2020
DOI: 10.1016/j.jare.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 promotes acoustic wave-mediated BBB opening via Ca2+/PKC-δ pathway

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 72 publications
(111 reference statements)
0
15
0
Order By: Relevance
“…Possibly actin cytoskeleton passed the force to trigger the ER Ca 2+ signals ( Kim et al, 2015 ), which is also suggested from our data ( Figures 5A–E ). Ca 2+ signals can further activate PKC to induce Ras-Raf-MEK-ERK pathway ( Liao et al, 2020 ; Yan et al, 2020 ), and our data showed that inhibition of Ras truly blocked the mechanical activation of ERK ( Figures 5D,E ). These data indicate that actin cytoskeleton belongs to the mechanosensing component for ERK activation.…”
Section: Discussionmentioning
confidence: 56%
“…Possibly actin cytoskeleton passed the force to trigger the ER Ca 2+ signals ( Kim et al, 2015 ), which is also suggested from our data ( Figures 5A–E ). Ca 2+ signals can further activate PKC to induce Ras-Raf-MEK-ERK pathway ( Liao et al, 2020 ; Yan et al, 2020 ), and our data showed that inhibition of Ras truly blocked the mechanical activation of ERK ( Figures 5D,E ). These data indicate that actin cytoskeleton belongs to the mechanosensing component for ERK activation.…”
Section: Discussionmentioning
confidence: 56%
“…Our previous studies proved that SW effectively induces BBB opening without UCAs or microbubbles ( 26 , 34 ). In addition, the current research demonstrates that SW effectively opened the BBB without causing tissue damage ( Figures 2A–C ).…”
Section: Resultsmentioning
confidence: 98%
“…The molecular mechanism of using SW to open the blood-brain barrier is not fully understood. In addition to the aforementioned computational studies, our previous research indicated that SW can activate TRPV4 channels on vascular endothelial cells membrane to promote C 2+ influx into endothelial cells and then activate the PKCdelta signaling pathway, which finally leads to the disruption of tight junctions ( 34 ). Adding TRPV4 agonists was shown to reduce the necessary SW intensity, which may help to reduce tissue damage caused by excessive mechanical force of SW in future applications.…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation on US neuromodulation mechanism relies in two aspects, namely, physical mechanism and neuronal mechanism. In terms of the neuronal mechanism, many studies have investigated the role of various mechanosensitive ion channels in US stimulation [46][47][48][49][50]; however, their conclusions are inconsistent and inconclusive. A more comprehensive study is still required to uncover the neuronal mechanism of US stimulation of the retina.…”
Section: Discussionmentioning
confidence: 99%